KREATIVITAS GURU DALAM PENGGUNAAN MEDIA PEMBELAJARAN PADA MATA PELAJARAN RUMPUN PENDIDIKAN AGAMA ISLAM DI MI NEGERI WATUAGUNG TAMBAK BANYUMAS - Pujiwantoro, Zaenal Arif (IAIIG Cilacap, 2018)
Learning media is anything that delivers messages from sources to recipients in the context of the interaction of teaching and learning, teachers should be able to use or use them either as a teaching aid or as a medium of learning.In the use of religious learning media, teachers should be able to adjust the material characteristics that will be presented and can attract students' attention, and not contrary to the religious shari'ah or not violate religious ethics. Departing from the problems above, then in general the problems formulated in this research is, how is the use of learning media at MI Negeri Watuagung Tambak Banyumas? The research that the author did in MI Negeri Watuagung Tambak Banyumas is included in qualitative descriptive research. In the course of collecting data, the author uses the method of observation, interview, and documentation. As for the analysis, the authors use descriptive qualitative analysis techniques, namely in the form of data written or oral from people and perpetrators observed so that in this case the author seeks to conduct research that is describe thoroughly about the actual situation. From the results of this study, it can be concluded that in the process of learning PAI in MI Negeri Watuagung Tambak Banyumas teachers using learning media. But depending on the learning materials (conditional). Besides, in using the existing learning media and using methods in accordance with the material that will convey, that is tailored to the material, objectives, methods, characteristics of students in class, it is intended that the use of learning media does not deviate from the material so that students' understanding with the use learning media can be more easily achieved. The types of media used by PAI teachers in MI Negeri Watuagung Tambak Banyumas include: blackboards, LCD Projectors, LKS, package books, Al-Quran and translations, CDs, VCDs, Television. Teachers use various variations in the use of instructional media, including media and material heard, media and materials viewed as well as media and materials that can be touched or manipulated (active media).Keywords: Use of Learning Media, Islamic Religious Education